A Human Clinical, Histological, Histomorphometrical, and Radiographical Study on Biphasic HA‐Beta‐TCP 30/70 in Maxillary Sinus Augmentation. (4th September 2013) - Mangano, Carlo; Sinjari, Bruna; Shibli, Jamil A.; Mangano, Francesco; Hamisch, Sabine; Piattelli, Adriano; Perrotti, Vittoria; Iezzi, Giovanna
Abstract Background By mixing hydroxyapatite (HA) and tricalcium phosphate (TCP), biphasic calcium phosphate ceramics can be obtained, and by varying their ratio it is possible to tailor the characteristics of the biomaterial. Purpose The aim of the present human study was to evaluate the histological and radiographical aspects of bone formation in maxillary sinus augmentation using a 30/70 HA‐beta‐TCP with a reticular structure. Materials and Methods A total of 12 patients, undergoing two‐stage sinus augmentation procedure using HA‐beta‐TCP at a ratio of 30/70, were included in the present study. After a 6‐month healing period, during implant insertion, radiographical analysis was performed, and then the bone core biopsies were harvested and processed for histology. Results At radiographic evaluation, the bone gain was on average 6.85 ± 0.60 mm. HA‐beta‐TCP 30/70 appeared to be lined by newly formed bone, with no gaps at the interface. The histomorphometric analysis revealed 26 ± 2% of residual grafted biomaterial, 29 ± 3% of newly formed bone, and 45 ± 2% of marrow spaces. Conclusions The present results indicate histologically the high biocompatibility and osteoconductivity of HA‐beta‐TCP 30/70, and clinically its successful use for sinus augmentation procedures.